2008
DOI: 10.1590/s0004-282x2008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis: combined nutritional, respiratory and functional assessment

Abstract: -Objective:To establish correlations between nutritional, functional and respiratory indices of patients with amyotrophic lateral sclerosis (ALS). Method: Twenty patients (13 appendicular -GA and 7 bulbar -GB) were included in the multidisciplinary study at the Neurological Clinic Ambulatory of the University of Campinas Hospital. Results: Among the GA type significant correlation was observed between maximal inspiratory (MIP) and expiratory (MEP) pressure (r= -0.76), MEP and pulse oxymetry (r=0.58), MIP and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(23 reference statements)
2
9
0
1
Order By: Relevance
“…The results found in this study corroborate those obtained by Silva et al 19 who also found correlation between BMI and FVC and between BMI and MEP in patients who presented with bulbar ALS. The correlation was strong, even considering MIP and MEP indicators are not a sensitive measure in the evaluation of the respiratory function in these patients, due to oro-pharyngeal weakness, as described by Fitting et al 20 .…”
Section: Resultssupporting
confidence: 92%
“…The results found in this study corroborate those obtained by Silva et al 19 who also found correlation between BMI and FVC and between BMI and MEP in patients who presented with bulbar ALS. The correlation was strong, even considering MIP and MEP indicators are not a sensitive measure in the evaluation of the respiratory function in these patients, due to oro-pharyngeal weakness, as described by Fitting et al 20 .…”
Section: Resultssupporting
confidence: 92%
“…ALSFRS-R is a reliable tool useful to predict survival in ALS 30,31 , survival after mechanical non-invasive ventilation, and to estimate overall functioning of patients with ALS 32 . ALSFRS-R scores did not change among supplemented patients (p=0.173), but significantly declined in the control group (p=0.003).…”
mentioning
confidence: 99%
“…Anthropometry involves obtaining measures of body size, their proportions and the relationship with standards that reflect the development of adult subjects. The most used measures are weight, height, circumferences and skinfolds (Almeida et al, 2010;Silva et al, 2008b;Silva et al, 2008c;Stanich et al, 2004;Kasarskis et al, 1996;Slowie et al, 1983).…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…Prior to patient's weighing, the wheelchairs are weighted and their weight is deducted at the time of calibration of the scale. In patients able to walk, the body weight is measured standing on platform type or digital scales (Silva et al, 2008b;Stanich et al, 2004). The weight can also be measured in chair scales, available in the market.…”
Section: Weight (W)mentioning
confidence: 99%